Malinche and the Conquest of Mexico. An Attempt at Historical Reconstruction - A. V. Sadikov (Ибероамериканские тетради, 2025)
The author sets forward a hypothesis of his own (though based on reliable sources) of the course of events that led to the subdual or, more exactly, to the loss of power of the Aztec Empire over what is now Mexico and the fall of the land under control by Spain. This version sustains that the campaign endeavored by Cortés against Tenochtitlan was only another episode of a whole series of wars waged by indigenous tribes against the Empire, wars that culminated in the victory of the former. The arrival of Cortés’ expeditionary force decided the outcome of the confrontation in which the Spaniards posed as the unifying link of a coalition of antiaztec forces that launched a full-scale offensive on the capital city of the Empire. Yet it was Malinche, a woman of noble Aztec descent, who became the actual mastermind of the Coalition. Nominally she acted as Cortés’ interpreter and made a superb performance, compensating for the captain’s crass ignorance of all things related to the New World. She made full use of her expert knowledge of the political situation, as well as of her freedom of expression (in absence of any outer control) in the interpretation of the negotiators’ standpoints, since no other participant could contrast her version of any statement with the original. The same woman also acted as the chief intelligence officer operating in the best interest of Cortés’ staff, as she was the only one who could talk with scouts and local residents piecing together all bits of information concerning the moves and plans of the enemy throughout the whole campaign. And it was her brilliant performance in both the above-mentioned roles that ensured the final victory of the Coalition.